Managing social-educational robotics for students with autism spectrum disorder through business model canvas and customer discovery - Arora, Anshu Saxena; Arora, Amit; Sivakumar, K.; McIntyre, John R. (Frontiers in Robotics and AI, 2024)
Social-educational robotics, such as NAO humanoid robots with social, anthropomorphic, humanlike features, are tools for learning, education, and addressing developmental disorders (e.g., autism spectrum disorder or ASD) through social and collaborative robotic interactions and interventions. There are significant gaps at the intersection of social robotics and autism research dealing with how robotic technology helps ASD individuals with their social, emotional, and communication needs, and supports teachers who engage with ASD students. This research aims to (a) obtain new scientific knowledge on social-educational robotics by exploring the usage of social robots (especially humanoids) and robotic interventions with ASD students at high schools through an ASD studentteacher co-working with social robot-social robotic interactions triad framework; (b) utilize Business Model Canvas (BMC) methodology for robot design and curriculum development targeted at ASD students; and (c) connect interdisciplinary areas of consumer behavior research, social robotics, and human-robot interaction using customer discovery interviews for bridging the gap between academic research on social robotics on the one hand, and industry development and customers on the other. The customer discovery process in this research results in eight core research propositions delineating the contexts that enable a higher quality learning environment corresponding with ASD students' learning requirements through the use of social robots and preparing them for future learning and workforce environments. .Social robots, especially humanoids, are popular with humans due to their anthropomorphic, humanlike features and their capability to perform autonomous movements, sensory-motor tasks, and verbal and non-verbal communications (Zhang et al., 2019;Arora, Parnell, and Arora, 2022;Bertacchini et al., 2022). Social robotics researchers have defined 'social robots' in the HRI literature as 'sociable' (i.e., robots can be used as tools/aid for social cognition), 'socially evocative' (i.e., robots are anthropomorphic and evoke positive feelings in humans during human-robot interaction), 'socially intelligent' (i.e., robots portray social intelligence and exhibit models of social competence and human cognition), 'socially situated' (i.e., robots are intelligent beings and can distinguish objects and other social agents in their social space), and 'socially interactive' (i.e., robots can be utilized for peer-to-peer HRI for social interaction and interventions with humans) agents (Roesler,